2017
DOI: 10.14207/ejsd.2017.v6n3p20
|View full text |Cite
|
Sign up to set email alerts
|

Are People Willing to Pay for Eco-Labeled Wild Seafood? An Overview

Abstract: In the last two decades, eco-labeled seafood has been becoming an instrument of sustainability directed towards consumers, addressing a market-based incentive for better management of fisheries. In this context, several studies across the countries have been conducted about how much consumers are willing to pay for fish caught by certifiably sustainable fishing activities. In this direction, the aim of this study was to systematize the available information about the willingness-topay (WTP) more for eco-labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…3 Model results show quite clearly that the tuna species "Yellow fin" impacts positively on consumer preference, even if consumers usually are not aware of the differences among fish species, as stated by Burger and Gochfeld (2009) and Gaviglio et al (2014). Moreover, findings show that the type of preservative used for canned tuna, both "canned in olive oil and "canned in extra virgin olive oil", impact positively on the probability of choosing such a product, as well as brands, confirming the important role of such attributes on consumer quality perceptions (Vitale et al, 2017). Consumer aversion to higher prices, which is corroborated by our results, seems to be related to the age of the consumers (the older the consumer, the higher the aversion).…”
Section: Random Utility Modelmentioning
confidence: 73%
“…3 Model results show quite clearly that the tuna species "Yellow fin" impacts positively on consumer preference, even if consumers usually are not aware of the differences among fish species, as stated by Burger and Gochfeld (2009) and Gaviglio et al (2014). Moreover, findings show that the type of preservative used for canned tuna, both "canned in olive oil and "canned in extra virgin olive oil", impact positively on the probability of choosing such a product, as well as brands, confirming the important role of such attributes on consumer quality perceptions (Vitale et al, 2017). Consumer aversion to higher prices, which is corroborated by our results, seems to be related to the age of the consumers (the older the consumer, the higher the aversion).…”
Section: Random Utility Modelmentioning
confidence: 73%
“…While eco-labelled seafood is generally perceived to be in a different category compared to fish products in general, consumers can be considered to possess a species-specific WTP [30,[35][36][37]. Indeed, WTP would differ based on the seafood product, the initial price, the countries, and the consumers' sociodemographic characteristics [8,16,[23][24][25][26]30,31,36,38]. Italian hypermarket consumers in this study showed an average WTP for anchovy eco-labels of 19% for WTP-LIH and 24% for WTP-BFG in Palermo and 16% for WTP-LIH and 18% for WTP-BFG in Milan.…”
Section: Discussionmentioning
confidence: 99%
“…In his study he measured the preferences and willingness of consumers to pay for coffee labeled certification in Taiwan, with certification results that are easily known, organic, the level of certification of products that are environmentally friendly, and shows that fair trade will make consumers willing to pay more. Ecolabeling tends to be an important factor in influencing consumer purchasing decisions, when the price of green products is relatively expensive or of low quality, in other words the product attributes of ecolabels have a dominant role compared to other product attributes [30] when consumers will decide to buy it at a higher price than conventional products.. Research shows the same results, that consumers are willing to pay more for the price of electrocable products, such as 43-inch LED TVs for consumers in Korea [25] , and seafood [34]. From this description, I propose the following hypothesis : H2 : Ecolabel is thought to influence the Consumers' Willingness to Pay More.…”
Section: Literature Reviewmentioning
confidence: 75%